2020
DOI: 10.1523/jneurosci.2090-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

A Central Amygdala-Globus Pallidus Circuit Conveys Unconditioned Stimulus-Related Information and Controls Fear Learning

Abstract: The central amygdala (CeA) is critically involved in a range of adaptive behaviors. In particular, the somatostatin-expressing (Sst + ) neurons in the CeA are essential for classic fear conditioning.These neurons send long-range projections to several extra-amygdala targets, but the functions of these projections remain elusive. Here, we found in mice that a subset of Sst + CeA neurons send projections to the globus pallidus external segment (GPe), and constitute essentially the entire GPe-projecting CeA popul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 65 publications
1
24
0
Order By: Relevance
“…Recent literature emphasized that PV + neurons are at the intersection of motor-anxiety circuits (Sztainberg et al, 2011; Hunt et al, 2018; Giovanniello et al, 2020); we do not currently know the downstream targets that mediate the anxiety-related response. As the STN does not mediate this anxiety-related response, other descending pathways such as the direct projections to the raphe (Pollak Dorocic et al, 2014) or their indirect projection to the habenula via the internal globus pallidus (Smith et al, 1998; Wallace et al, 2017) could be involved.…”
Section: Discussionmentioning
confidence: 96%
“…Recent literature emphasized that PV + neurons are at the intersection of motor-anxiety circuits (Sztainberg et al, 2011; Hunt et al, 2018; Giovanniello et al, 2020); we do not currently know the downstream targets that mediate the anxiety-related response. As the STN does not mediate this anxiety-related response, other descending pathways such as the direct projections to the raphe (Pollak Dorocic et al, 2014) or their indirect projection to the habenula via the internal globus pallidus (Smith et al, 1998; Wallace et al, 2017) could be involved.…”
Section: Discussionmentioning
confidence: 96%
“…Recent literature emphasized that PV + neurons are at the intersection of motor-anxiety circuits (Sztainberg et al, 2011;Hunt et al, 2018;Giovanniello et al, 2020); we do not currently know the downstream targets that mediate the anxiety-related response. As the STN does not mediate this anxiety-related response, other descending pathways such as the direct projections to the raphe (Pollak Dorocic et al, 2014) or their indirect projection to the habenula via the internal globus pallidus (Smith et al, 1998;Wallace et al, 2017) could be involved.…”
Section: Beyond Go and No-go?mentioning
confidence: 95%
“…In addition, cellular changes in the amygdala have been reported in ASD (Amaral et al, 2008). In a recent study (Giovanniello et al, 2020), we found that a subpopulation of neurons in the CeA send direct projections to the GPe, and the CeA-GPe pathway conveys US information and controls learning during fear conditioning. In the current study, we found that an enhanced excitatory drive onto GPe-projecting CeA neurons parallels the anxiety phenotypes of female 16p11.2 del /+ mice.…”
Section: Discussionmentioning
confidence: 89%
“…We recently identified a pathway from the CeA to the globus pallidus externa (GPe), which conveys information of the US and is critical for learning in fear conditioning (Giovanniello et al, 2020). Importantly, optogenetic activation of the CeA-GPe pathway increases fear generalization whereby animals increase their freezing to CS–.…”
Section: Resultsmentioning
confidence: 99%